Sulfur-based active material, electrode, lithium-ion secondary battery, and manufacturing method
The manufacturing process of sulfur-based active materials using acrylic resin and iron compounds addresses volume energy density and cycle characteristics issues, enhancing lithium-ion battery performance by maintaining capacity and reducing capacity loss over cycles.
Patent Information
- Application Number
- JP2024511902
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-20
AI Technical Summary
Existing sulfur-based active materials for lithium-ion secondary batteries suffer from reduced volume energy density and poor cycle characteristics due to large volume changes during lithium ion absorption and release, and carbon materials like graphite and hard carbon have reached theoretical capacity limits.
A manufacturing process involving the mixing of acrylic resin, sulfur, and iron compounds containing divalent or trivalent iron ions, followed by firing at controlled temperatures, results in a sulfur-based active material with a reduced median diameter of the iron compound, enhancing volume energy density and cycle characteristics.
The process maintains high capacity maintenance rates and improves cycle characteristics by reducing the decrease in charging and discharge capacity over repeated cycles, resulting in lithium-ion secondary batteries with enhanced performance.
Smart Images

Figure 0007622902000004 
Figure 0007622902000001 
Figure 0007622902000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel sulfur-based active material, an electrode comprising the sulfur-based active material, a lithium-ion secondary battery comprising the electrode, and methods for producing the same. [Background technology]
[0002] Lithium-ion secondary batteries have a large charge / discharge capacity and are primarily used as batteries for portable electronic devices. They are also increasingly being used as batteries for electric vehicles, and there are high hopes for improved performance.
[0003] Patent Document 1 describes a sulfur-based active material obtained by firing a raw material containing sulfur and a polymer containing methacrylonitrile as a monomer component.
[0004] On the other hand, it has been proposed to increase the battery capacity of lithium-ion secondary batteries by using materials capable of absorbing and releasing more lithium ions, such as silicon (Si) and tin (Sn), as the negative electrode active material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-167144 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, active materials using polymers such as those in Patent Document 1 tend to have low true densities, and therefore, even if the charge / discharge capacity per unit mass is large, they tend to be inferior when compared in terms of charge / discharge capacity per unit volume (volumetric energy density).
[0007] In addition, the above-mentioned materials proposed as negative electrode active materials have a problem that the volume change caused by the absorption and release of lithium ions is large, so that the cycle characteristics when repeatedly charged and discharged are not good. Carbon materials such as graphite and hard carbon are also used, but they have already reached the theoretical capacity, and a significant improvement in capacity cannot be expected.
[0008] The present invention provides a novel sulfur-based active material that maintains a capacity retention rate and also has a good volumetric energy density, an electrode comprising the sulfur-based active material, i.e., a positive electrode or a negative electrode, a lithium ion secondary battery comprising the electrode, and methods for producing the same. [Means for solving the problem]
[0009] The present invention relates to (1) a step of mixing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions to obtain a raw material; and (2) A step of calcining the raw material A method for producing a sulfur-based active material comprising: The method for producing the iron compound, wherein the median diameter of the iron compound is 12.00 μm or less. Regarding. Effect of the Invention
[0010] According to the present invention, it is possible to provide a novel sulfur-based active material that maintains a capacity retention rate and also has a good volumetric energy density, an electrode including the sulfur-based active material, i.e., a positive electrode or a negative electrode, a lithium ion secondary battery including the electrode, and methods for producing the same.
[0011] In this specification, the term "cycle characteristic" refers to the characteristic of maintaining the charge / discharge capacity of a secondary battery despite repeated charging and discharging. Therefore, a secondary battery that experiences a large decrease in charge / discharge capacity and a low capacity retention rate with repeated charging and discharging has poor cycle characteristics, whereas a secondary battery that experiences a small decrease in charge / discharge capacity and a high capacity retention rate has excellent cycle characteristics. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a cross-sectional view that illustrates a reaction apparatus used in the production of a sulfur-based active material in the examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The configuration of the present invention will be described in detail below. The upper and lower limit values of "more than", "less than", "over", "less than", etc. in the description of a numerical range can be arbitrarily combined, and the numerical values in the examples can be these upper and / or lower limits. In addition, a numerical range shown as including a lower limit or an upper limit is understood to simultaneously disclose a numerical range not including the upper limit or lower limit, as long as it is not contrary to the spirit of the present invention, and conversely, a numerical range shown as not including a lower limit or an upper limit is understood to simultaneously disclose a numerical range including the lower limit or upper limit, as long as it is not contrary to the spirit of the present invention.
[0014] One embodiment of the present invention is a method for producing a sulfur-based active material, comprising: (1) mixing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions to obtain a raw material; and (2) firing the raw material, wherein the median diameter of the iron compound is 12.00 μm or less.
[0015] In the production method of the present invention, by reducing the median diameter of the iron compound, it is possible to obtain a sulfur-based active material that has a good volumetric energy density while maintaining the capacity retention rate.
[0016] The content of the iron compound containing divalent or trivalent iron ions in the raw material is preferably 50 parts by mass or more and 300 parts by mass or less with respect to 100 parts by mass of the acrylic resin.
[0017] The step (1) preferably includes the steps of: (1-a-1) introducing the acrylic resin and the iron compound containing divalent or trivalent iron ions into an organic solvent and mixing them to obtain a liquid mixture; (1-a-2) removing the organic solvent from the liquid mixture to obtain a dry mixture; and (1-a-3) mixing the dry mixture with sulfur.
[0018] The step (1) preferably includes the step (1-b) of mixing the acrylic resin, the sulfur, and the iron compound containing divalent or trivalent iron ions, all in a powder state.
[0019] The firing temperature in step (2) is preferably higher than 250°C and lower than 550°C.
[0020] The firing temperature in the step (2) is preferably higher than the temperature at which the iron compound containing divalent or trivalent iron ions thermally decomposes.
[0021] The content of the sulfur in the raw material is preferably more than 50 parts by mass and less than 1,000 parts by mass with respect to 100 parts by mass of the acrylic resin.
[0022] The acrylic resin is preferably at least one polymer selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one polymer selected from the group consisting of polymers of at least one compound selected from the group consisting of acrylate compounds represented by the above formula (1) and at least one compound selected from the group consisting of diacrylate compounds represented by the above formula (2). CH2=C(R 11 )COOR 12 (1) (where R 11 is a hydrogen atom or a methyl group, and R 12 is an alkyl group. CH2=C(R 21)COO-Y-OCO(R 22 )C=CH2(2) (where R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms.
[0023] R 12 is an alkyl group having 1 to 6 carbon atoms, and Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, and in the hydrocarbylene group, the number of substituents is preferably 1 to 4, the alkyl substituent group has 1 to 4 carbon atoms, and the carbon skeleton constituting the hydrocarbylene group has 1 to 2 ether bonds.
[0024] Another embodiment of the present invention is a method for producing an electrode, comprising the steps of: producing a sulfur-based active material by the method for producing a sulfur-based active material; and (3) producing an electrode by a conventional method using the sulfur-based active material.
[0025] Another embodiment of the present invention is a method for producing a lithium ion secondary battery, comprising the steps of: producing an electrode by the above-described method for producing an electrode; and (4) using the electrode to produce a lithium ion secondary battery by a conventional method.
[0026] Another embodiment of the present invention is a sulfur-based active material obtained by firing a raw material including an acrylic resin, sulfur, and an iron compound including divalent or trivalent iron ions, and including at least carbon, sulfur, and iron as constituent elements, wherein the iron compound has a median diameter of 12.00 μm or less, the material includes iron disulfide, and the content of sulfur as a constituent element is 40.0 mass% or more.
[0027] In X-ray diffraction measurement using CuKα radiation, the sulfur-based active material preferably has a half-width of 0.20° or more of a peak showing maximum diffraction intensity within a range of 2θ=33.04° (±1.0°).
[0028] The sulfur-based active material has a true density of 2.4 g / cm 3 Super 3.6g / cm 3 It is preferable that it is less than 1000 .mu.m.
[0029] The sulfur-based active material preferably has a carbon content of more than 5.0% by mass and less than 30.0% by mass.
[0030] It is preferable that the sulfur-based active material has peaks at 2θ=25.5° (±1.0°), 28.51° (±1.0°), 33.04° (±1.0°), 37.07° (±1.0°), 40.76° (±1.0°), 47.42° (±1.0°), and 56.27° (±1.0°) in X-ray diffraction measurement using CuKα radiation.
[0031] The acrylic resin is preferably at least one polymer selected from the group consisting of acrylate compounds represented by the above formula (1), or at least one polymer selected from the group consisting of polymers of at least one compound selected from the group consisting of acrylate compounds represented by the above formula (1) and at least one compound selected from the group consisting of diacrylate compounds represented by the above formula (2).
[0032] R 12 is an alkyl group having 1 to 6 carbon atoms, and Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, and in the hydrocarbylene group, the number of substituents is preferably 1 to 4, the alkyl substituent group has 1 to 4 carbon atoms, and the carbon skeleton constituting the hydrocarbylene group has 1 to 2 ether bonds.
[0033] The sulfur-based active material preferably has a median diameter of 1 μm or more and 40 μm or less.
[0034] The content of the iron compound containing the divalent or trivalent iron ion and the content of the sulfur in the raw material are preferably 50 parts by mass or more and 300 parts by mass or less, and more than 50 parts by mass but less than 1,000 parts by mass, relative to 100 parts by mass of the acrylic resin.
[0035] <Raw materials> (Acrylic resin) In the present invention, the acrylic resin is at least one polymer selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one polymer selected from the group consisting of polymers of at least one compound selected from the group consisting of acrylate compounds represented by the following formula (1) and at least one compound selected from the group consisting of diacrylate compounds represented by the following formula (2). CH2=C(R 11 )COOR 12 (1) (where R 11 is a hydrogen atom or a methyl group, and R 12 is an alkyl group. CH2=C(R 21 )COO-Y-OCO(R 22 )C=CH2(2) (where R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms.
[0036] In formula (1), R 11 is preferably a methyl group, R 12is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and among these, a methyl group, an n-butyl group, an i-butyl group, or a t-butyl group is preferable. Examples of the compound represented by formula (1) include methyl (meth)acrylate, butyl (meth)acrylate, and the like, and more preferably, methyl methacrylate and butyl methacrylate are mentioned. Here, the "(meth)acrylate" of methyl (meth)acrylate and butyl (meth)acrylate means either "acrylate" or "methacrylate" (hereinafter the same). A more preferable example of the compound represented by formula (1) is butyl methacrylate.
[0037] In formula (2), R 21 and R 22 are preferably a methyl group. The carbon number of the hydrocarbylene group (straight chain) of Y is preferably 2 to 6, more preferably 2 or 3. The number of the substituents of Y is preferably 1 to 4, more preferably 1 or 2. The substituents of Y are preferably one or more substituents selected from the group consisting of a hydroxyl group and an alkyl group having 1 to 4 carbon atoms, and the alkyl group having 1 to 4 carbon atoms is preferably a methyl group. When the carbon skeleton of Y has an ether bond through an oxygen atom, for example, the portion corresponding to -YO- is preferably represented by the following formula (3) (however, in formula (3), the substituents of Y are not taken into consideration). -(CH2) l -(CH2CH2O) m -(CH2CH2CH2O) n - (3) (Here, l is 0 to 6, m is 0 to 3, and n is 0 to 2. However, l, m, and n cannot all be 0 at the same time.)
[0038] In formula (3), it is preferred that l is 1, 2, 3, 4, 5 or 6, and m and n are 0; alternatively, m is 1, 2 or 3, and l and n are 0; or alternatively, n is 1 or 2, and l and m are 0.
[0039] Examples of the compound represented by formula (2) include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyne glycol di(meth)acrylate, glycerin di(meth)acrylate, etc. Among these, ethylene glycol dimethacrylate is preferred.
[0040] Preferred examples of the acrylic resin include homopolymers of methyl (meth)acrylate, homopolymers of butyl (meth)acrylate, copolymers of methyl (meth)acrylate and ethylene glycol di(meth)acrylate, and copolymers of butyl (meth)acrylate and ethylene glycol di(meth)acrylate. Of these, the acrylic resin is preferably a methacrylate type. More preferred examples of the acrylic resin include copolymers of butyl methacrylate and ethylene glycol dimethacrylate.
[0041] One or more kinds of acrylic resins can be used.
[0042] [Form of acrylic resin] In the present invention, the acrylic resin is preferably in the form of fine particles. Here, fine particles refer to particles having a particle diameter of 300.0 μm or less. The particle diameter is preferably 270.0 μm or less, more preferably 200.0 μm or less, even more preferably 100.0 μm or less, even more preferably 50.0 μm or less, even more preferably 20.0 μm or less, even more preferably 15.0 μm or less, even more preferably 13.0 μm or less, even more preferably 10.0 μm or less, even more preferably 6.0 μm or less. On the other hand, the lower limit of the particle diameter is not particularly limited, but is usually, for example, 0.1 μm or more, preferably 1.0 μm or more. The particle diameter is a value (median diameter) measured by a precision particle size distribution measuring device Multisizer 3 manufactured by Beckman Coulter Co., Ltd.
[0043] The acrylic resin may be spherical fine particles or porous fine particles. When the acrylic resin is porous, its oil absorption is preferably 100mL / 100g or more, more preferably 110mL / 100g or more, even more preferably 120mL / 100g or more, even more preferably 130mL / 100g or more, and even more preferably 140mL / 100g or more. The oil absorption is a value measured according to JIS K 5101-13-2:2004. More specifically, it can be measured by the method of paragraph 0069 of JP2017-88501A.
[0044] [Weight average molecular weight of acrylic resin (Mw)] The Mw of the acrylic resin is not particularly limited as long as it has the above structure. However, the Mw of the acrylic resin is usually in the range of more than 2000 and less than 1,500,000. The Mw is a value measured by gel permeation chromatography (GPC) (calibrated with polystyrene).
[0045] [Acquisition or production of acrylic resin] The acrylic resins are commercially available or can be prepared by conventional methods within the knowledge of one skilled in the art. Commercially available acrylic resins include, for example, those manufactured by Sekisui Plastics Co., Ltd.
[0046] (sulfur) As the sulfur, any of various forms such as powdered sulfur, insoluble sulfur, precipitated sulfur, colloidal sulfur, etc. can be used, of which precipitated sulfur and colloidal sulfur are preferred.
[0047] The sulfur content is preferably more than 50 parts by mass, more preferably more than 100 parts by mass, more preferably more than 300 parts by mass, more preferably more than 400 parts by mass, and more preferably more than 500 parts by mass, relative to 100 parts by mass of the acrylic resin. By being more than 50 parts by mass, the charge / discharge capacity and cycle characteristics tend to be improved. On the other hand, there is no particular upper limit for the sulfur content, but it is usually preferably less than 1000 parts by mass, more preferably less than 900 parts by mass, more preferably less than 800 parts by mass, and more preferably less than 700 parts by mass. By being 1000 parts by mass or less, there is a tendency that it is advantageous in terms of cost.
[0048] Although any of various allotropes of sulfur can be used, it is preferable that the sulfur contains S8 sulfur, which is solid at room temperature and pressure, and it is more preferable that the sulfur is S8 sulfur alone.
[0049] (Iron compounds containing divalent or trivalent iron ions) The iron compound containing divalent or trivalent iron ions is not particularly limited as long as it decomposes during firing and reacts with sulfur to generate iron disulfide, and various compounds can be used. Examples of such iron compounds include iron acid salts and iron complexes. Examples of iron acid salts include both organic iron acid salts and inorganic iron acid salts. On the other hand, examples of iron complexes include neutral iron complexes and salts of iron complex ions (iron complex salts).
[0050] Examples of organic acid salts of iron include divalent iron (Fe2+ ) and organic acid salts, and trivalent iron (Fe 3+ ) and an organic acid salt. Among these, a salt of divalent iron and an organic acid is preferred. The organic acid is not particularly limited to those having a carboxyl group (-COOH) or those having a sulfo group (-SO3H), but those having a carboxyl group are preferred. Specific examples of the organic acid include fatty acids, oxalic acid, tartaric acid, citric acid, malic acid, and succinic acid. Specific examples of fatty acids include those having 1 to 6 carbon atoms, such as acetic acid, propionic acid, and butyric acid. Among these, acetic acid, oxalic acid, and the like are preferred. Preferred examples of the organic acid salt of iron include iron(II) acetate and iron(II) oxalate. These may be hydrates. One or more types of organic acid salt of iron can be used.
[0051] Examples of inorganic salts of iron include divalent iron (Fe 2+ ) and inorganic acid salts, and trivalent iron (Fe 3+ ) and an inorganic acid. Specific examples of inorganic acids include hydrochloric acid, sulfuric acid, and nitric acid. Of these, nitric acid is preferred. Preferred examples of inorganic acid salts of iron include iron chloride (II), iron chloride (III), iron sulfate (II), iron sulfate (III), iron nitrate (II), and iron nitrate (III). These may be hydrates. One or more inorganic acid salts of iron may be used.
[0052] As an example of an iron complex, divalent iron (Fe 2+ ) complexes and trivalent iron (Fe 3+) complexes. The iron complex may be in the form of a neutral complex or a complex salt. The ligand coordinated to the iron ion is not particularly limited, and examples thereof include halogen atoms such as chlorine and bromine atoms, cyano groups, dicyclopentadienyl groups, and N,N'-bis(salicylidene)ethylenediamine. Examples of the iron complex include potassium hexacyanidoferrate(II) ([Fe(CN)6]K4), potassium hexacyanidoferrate(III) ([Fe(CN)6]K3), sodium tetrachloroferrate(III) ([FeCl4]Na), dicyclopentadienyl iron(II) (ferrocene), and N,N'-bis(salicylidene)ethylenediaminatoiron(III) chloride. One or more types of iron complexes can be used.
[0053] As the iron compound containing divalent or trivalent iron ions, at least one selected from the group consisting of the above-mentioned organic acid salts of iron, inorganic acid salts of iron, neutral iron complexes, and iron complex salts can be used. Among these, organic acid salts of iron, inorganic acid salts of iron, and neutral iron complexes are preferred.
[0054] The median diameter (D50) of the iron compound containing divalent or trivalent iron ions is 12.00 μm or less. The median diameter is preferably 10.00 μm or less, more preferably 8.00 μm or less, even more preferably 6.00 μm or less, even more preferably 5.00 μm or less, even more preferably 4.50 μm or less, even more preferably 4.30 μm or less, even more preferably 4.29 μm or less, even more preferably 4.00 μm or less, even more preferably 3.00 μm or less. On the other hand, there is no particular restriction on the lower limit of the median diameter, but it is usually about 0.10 μm or more, may be about 1.00 μm, or may be about 2.00 μm. The median diameter can be measured by the method described in the Examples section below.
[0055] The specific surface area of iron compounds containing divalent or trivalent iron ions is 1.0 m 2 / g or more, and more preferably 2.0m 2 / g or more, more preferably 2.5m2 / g or more, more preferably 2.8m 2 / g or more, more preferably 3.0m 2 / g or more, more preferably 4.0m 2 / g or more, more preferably 4.2m 2 / g or more, more preferably 4.5m 2 On the other hand, there is no particular upper limit on the specific surface area, but it is usually 40.0 m 2 / g or less, and 2 / g or less, and 2 The specific surface area can be measured by a fully automatic specific surface area measuring device, Macsorb (HM-model 1201, manufactured by Mountec Co., Ltd.).
[0056] The iron compound having a median diameter of 12.00 μm or less can be prepared by a conventional method, for example, by pulverizing the iron compound with a pulverizer. Examples of such pulverizers that can be used include those manufactured by Japan Analytical Industry Co., Ltd. (e.g., JFC-2000, etc.), those manufactured by Labnect Co., Ltd. (e.g., Free Speed Mill FS-20, etc.), and those manufactured by Aisin Nano Technologies Co., Ltd. (e.g., Nano Jet Mizer NJ-30, etc.).
[0057] From the viewpoint of the effects of the present invention, the content of the iron compound containing divalent or trivalent iron ions is preferably 50 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the acrylic resin. The content is more preferably more than 50 parts by mass, even more preferably more than 60 parts by mass, even more preferably more than 70 parts by mass, and even more preferably more than 75 parts by mass. On the other hand, the content is more preferably less than 250 parts by mass, even more preferably less than 200 parts by mass, even more preferably less than 150 parts by mass, and even more preferably 100 parts by mass or less.
[0058] (Conductive carbon materials) The raw material may contain a carbon material having electrical conductivity. This is because the electrical conductivity of the sulfur-based active material can be improved. As such an electrically conductive carbon material, a carbon material having a graphite structure is preferable. As the carbon material, for example, those having a condensed aromatic ring structure such as carbon black, acetylene black, ketjen black, graphite, carbon nanotube (CNT), carbon fiber (CF), graphene, and fullerene can be used. As the electrically conductive carbon material, one or more kinds can be used.
[0059] Among them, acetylene black, carbon black, and ketjen black are preferable because they are inexpensive and have excellent dispersibility. A small amount of CNT or graphene may be used in combination with acetylene black, carbon black, or ketjen black. Such a combination system makes it possible to further improve the cycle characteristics of a lithium ion secondary battery without significantly increasing the cost. The amount of CNT or graphene used in combination is preferably 8% by mass or more and 12% by mass or less of the total amount of the conductive carbon material.
[0060] The content of the conductive carbon material is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, relative to 100 parts by mass of the acrylic resin. By having a content of 5 parts by mass or more, it tends to be easier to achieve the purpose of further improving the charge / discharge capacity and cycle characteristics. On the other hand, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less. By having a content of 50 parts by mass or less, the proportion of the structure containing sulfur in the sulfur-based active material does not relatively decrease, and it tends to be easier to achieve the purpose of further improving the charge / discharge capacity and cycle characteristics.
[0061] (Other materials) The raw material may optionally contain other materials commonly used in this field.
[0062] <Production of sulfur-based active materials> In the present invention, the sulfur-based active material can be produced by baking a raw material obtained by mixing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions.
[0063] (Process (1)) Step (1) is a step of mixing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions to obtain a raw material to be subjected to calcination. The mixing method is not particularly limited as long as it is a method that sufficiently mixes these components, but in the present invention, at least the following mixing method using a WET method in which mixing is performed using a solvent, or the DRY method in which mixing is performed without using a solvent can be mentioned as a preferred mixing method.
[0064] [WET method] In the present invention, the WET method refers to a method for preparing a raw material, (1-a-1) a step of adding the acrylic resin and the iron compound containing divalent or trivalent iron ions to an organic solvent and mixing them to obtain a liquid mixture; (1-a-2) removing the organic solvent from the liquid mixture to obtain a dry mixture; and (1-a-3) mixing the dry mixture with sulfur It includes.
[0065] In step (1-a-1), the method of adding the acrylic resin and the iron compound containing divalent or trivalent iron ions to the organic solvent is not particularly limited as long as they can be mixed to obtain a liquid mixture. For example, (1) the acrylic resin and the iron compound containing divalent or trivalent iron ions may be simultaneously added to the organic solvent and mixed, (2) the acrylic resin may be added to the organic solvent and mixed, and then the iron compound containing divalent or trivalent iron ions may be added and mixed, or (3) the iron compound containing divalent or trivalent iron ions may be added to the organic solvent and mixed, and then the acrylic resin may be added and mixed.
[0066] In step (1-a-1), the organic solvent may be any organic solvent commonly used in this field, and examples of such solvents include N-methyl-2-pyrrolidone, N,N-dimethylformaldehyde, alcohol, hexane, water, acetone, ethers such as tetrahydrofuran, etc. In addition, the organic solvent is preferably one that dissolves the acrylic resin, since this contributes to good mixing. These solvents may be used alone or in combination of two or more.
[0067] Mixing of the organic solvent with the acrylic resin and / or the iron compound containing divalent or trivalent iron ions can be carried out, for example, by stirring in a container such as a beaker.
[0068] In the step (1-a-2), the organic solvent can be removed by a conventional method, for example, by subjecting the liquid mixture to a drying method such as drying by heating, drying under reduced pressure, or drying by heating under reduced pressure.
[0069] The dry mixture thus obtained is preferably pulverized before being subjected to the next step. This is because it is expected that the mixing in step (1-a-3) can be more suitably performed by doing so. The pulverization can be performed by a conventional method, for example, by using a cutter mill or the like. In particular, it is preferable to perform coarse pulverization with a cutter mill and then fine pulverization with a freezing pulverizer.
[0070] The preferred particle size of the pulverized product is 1 μm or more in terms of median diameter, more preferably more than 1 μm, even more preferably more than 2 μm, even more preferably more than 3 μm, even more preferably more than 4 μm. The median diameter is preferably 40 μm or less, more preferably less than 40 μm, even more preferably less than 30 μm, even more preferably less than 20 μm, even more preferably less than 15 μm, even more preferably less than 10 μm. From the viewpoint of the effects of the present invention, the median diameter is preferably within the above range. The median diameter can be measured by the method described in the Examples section below.
[0071] In the step (1-a-3), the dry mixture and sulfur can be mixed by a conventional method, for example, a method of mixing them using a blender can be mentioned.
[0072] [DRY method] In the present invention, the DRY method refers to a method for preparing a raw material, (1-b) The method includes a step of mixing the acrylic resin, the sulfur, and the iron compound containing divalent or trivalent iron ions, all in a powder state.
[0073] Here, the powder refers to a state in which each solid raw material is sufficiently finely divided to a degree suitable for mixing under the purpose of the present invention. The size of the particles constituting the powder is not particularly limited as long as the mixing is carried out suitably, but the median diameter is usually, for example, in the range of 1 μm or more and 40 μm or less. From the viewpoint of the effect of the present invention, the size of the particles is preferably more than 1 μm, more preferably more than 2 μm, even more preferably more than 3 μm, and even more preferably more than 4 μm, while it is preferably 40 μm or less, more preferably less than 40 μm, more preferably less than 30 μm, even more preferably less than 20 μm, even more preferably less than 15 μm, and even more preferably less than 10 μm. The median diameter can be measured by the method described in the Examples section below.
[0074] The mixing can be carried out by a conventional method, for example, in the same manner as in the mixing in the above step (1-a-3).
[0075] In both the wet and dry methods, it is desirable to thoroughly mix the raw materials in advance. In addition, when a conductive carbon material or the like is added to the raw materials, these additives may be mixed in advance so that they are contained in the raw materials before firing.
[0076] The raw material thus obtained may be used as it is in the next step (2), or may be formed into pellets, if desired, and then used in step (2).
[0077] (Process (2)) Step (2) is a step of calcining the raw material obtained above. Calcination of the raw material can be performed by a conventional method, for example, by heating the raw material at a predetermined temperature increase rate until it reaches a predetermined temperature, maintaining the raw material at the predetermined temperature for a predetermined time, and then naturally cooling it.
[0078] [Non-oxidizing atmosphere] The firing is preferably carried out in a non-oxidizing atmosphere. The non-oxidizing atmosphere is an atmosphere that is substantially free of oxygen and is adopted to suppress oxidative deterioration and excessive thermal decomposition of the components. Specifically, it refers to an inert gas atmosphere such as nitrogen or argon, a sulfur gas atmosphere, etc. Therefore, the modification is carried out, for example, in a quartz tube under an inert gas atmosphere.
[0079] [Heating rate] The heating rate is preferably, for example, within the range of 50° C. / h or more and 500° C. / h or less. The heating rate is preferably more than 50° C. / h, more preferably more than 100° C. / h. On the other hand, the heating rate is preferably less than 500° C. / h, more preferably less than 400° C. / h, even more preferably less than 300° C. / h, and even more preferably less than 200° C. / h. When the heating rate is within such a range, it tends to be easier to achieve the purpose of improving the charge / discharge capacity and cycle characteristics.
[0080] [Firing temperature and time] The calcination temperature is the temperature after the temperature rise of the raw material is completed, and is maintained for a certain period of time for calcination of the raw material. The temperature is preferably in the range of more than 250°C and less than 550°C. By being more than 250°C, the sulfurization reaction tends to be avoided from being insufficient, and the charge / discharge capacity of the target product tends to be prevented from decreasing. On the other hand, by being less than 550°C, the decomposition of the raw material tends to be prevented, and the decrease in yield and the decrease in charge / discharge capacity tend to be prevented. The temperature is more preferably more than 300°C, more preferably more than 350°C, and even more preferably more than 380°C. On the other hand, less than 500°C is more preferable, less than 480°C is even more preferable, and even more preferably less than 450°C.
[0081] From the viewpoint of the effects of the present invention, the firing temperature in the step (2) is preferably higher than the temperature at which the iron compound containing divalent or trivalent iron ions thermally decomposes.
[0082] The time for maintaining the firing temperature may be appropriately set depending on the type of raw material, the firing temperature, etc., but is preferably, for example, 1 hour or more and 6 hours or less. By setting it to 1 hour or more, firing tends to proceed sufficiently, and by setting it to 6 hours or less, excessive thermal decomposition of the components tends to be prevented. The time is preferably more than 1 hour, more preferably more than 1.5 hours. On the other hand, the time is preferably less than 6 hours, more preferably less than 4 hours.
[0083] [Device] The calcination can be carried out by the apparatus shown in Fig. 1, or can be carried out by using a continuous apparatus such as a twin-screw extruder. When a continuous apparatus is used, there is an advantage that the sulfur-based active material can be produced continuously by a series of operations, such as kneading, pulverizing, and mixing the raw materials and calcining them in the apparatus.
[0084] (Residue removal process) In the treated product obtained after calcination, unreacted sulfur remains, which is the sulfur that sublimed during calcination and then cooled and precipitated. Since these residues are a factor in reducing cycle characteristics, it is desirable to remove them as much as possible. The removal of the residues can be carried out according to a conventional method, such as reduced pressure heating drying, hot air drying, and solvent washing.
[0085] (Crushing, classification) The obtained sulfur-based active material can be pulverized to a predetermined particle size and classified to obtain particles of a size suitable for the manufacture of electrodes. From the viewpoint of the effects of the present invention, the preferred particle size distribution of the particles is about 1 μm or more and 40 μm or less in terms of median diameter. The median diameter is preferably more than 1 μm, more preferably more than 2 μm, even more preferably more than 3 μm, and even more preferably more than 4 μm. The median diameter is preferably less than 40 μm, more preferably less than 30 μm, even more preferably less than 20 μm, even more preferably less than 15 μm, and even more preferably less than 10 μm. The median diameter can be measured by the method described in the Examples section below.
[0086] In the firing method using the twin-screw extruder described above, the sulfur-based active material can be produced and pulverized at the same time by shearing during kneading.
[0087] <Sulfur-based active material> The sulfur-based active material obtained above will be described below. The sulfur-based active material obtained above contains an acrylic resin modified with sulfur (acrylic resin sulfide) and iron disulfide, which are composite active materials, and contains at least carbon, sulfur, and iron as constituent elements. The sulfur content, carbon content, and hydrogen content shown below are the amounts of each element contained in the sulfur-based active material. In addition, the fact that the sulfur-based active material obtained above contains iron disulfide is based on a comparison with the peak profile of the diffraction intensity of iron disulfide (pyrite) obtained by X-ray diffraction measurement.
[0088] (Sulfur content) In the sulfur-based active material thus obtained, the preferred range of the sulfur content is more than 40.0 mass%, more preferably more than 45.0 mass%, even more preferably more than 50.0 mass%, and even more preferably more than 55.0 mass% in the sulfur-based active material. However, when a conductive carbon material is blended, even if the sulfur content is somewhat lower, due to the influence of the carbon constituting the conductive carbon material, the effect of improving the charge / discharge capacity and cycle characteristics may be expected. In such a case, the sulfur content may be about 5.0 mass% lower than the above-mentioned sulfur content.
[0089] (Carbon content) From the viewpoint of the effects of the present invention, the carbon content is preferably more than 5.0 mass% and less than 30.0 mass%. The carbon content is more preferably more than 6.0 mass%, further preferably more than 7.0 mass%, further preferably more than 8.0 mass%, and further preferably more than 8.5 mass%. On the other hand, the carbon content is more preferably less than 29.0 mass%, and further preferably less than 25.0 mass%.
[0090] (total sulfur and carbon content) The total content of carbon and sulfur in the sulfur-based active material is preferably more than 60% by mass, more preferably more than 65% by mass, while the total content is preferably less than 95% by mass, more preferably less than 90% by mass, and even more preferably less than 85% by mass.
[0091] (Hydrogen content) By baking, hydrogen (H) in the acrylic resin reacts with sulfur to become hydrogen sulfide, and is reduced from the sulfide. Therefore, the hydrogen content of the sulfur-based active material is preferably less than 1.00 mass%, more preferably less than 0.70 mass%, and even more preferably less than 0.50 mass%. When it is less than 1.00 mass%, there is a tendency that baking (sulfurization reaction) is sufficient. Therefore, in this case, the charge / discharge capacity tends to be improved.
[0092] (true density) From the viewpoint of the effect of the present invention, the true density of the sulfur-based active material is 2.4 g / cm 3 Super 3.6g / cm 3 The true density is preferably less than 2.5 g / cm 3 More preferably 2.6 g / cm 3 More preferably, 2.6 g / cm 3 On the other hand, the true density is more preferably 3.5 g / cm 3 less than 3.2 g / cm 3 less than 3.1 g / cm 3In the present invention, the true density refers to a density in the case where only the volume occupied by the sulfur-based active material itself is used as the volume for calculating the density, and specifically, the true density is calculated by the method described in the Examples section.
[0093] <Lithium-ion secondary battery> The sulfur-based active material of the present invention can be used as an electrode active material for a lithium ion secondary battery, that is, as a positive electrode active material or a negative electrode active material. That is, an electrode for a lithium ion secondary battery can be produced in the same manner as in the production of a general electrode for a lithium ion secondary battery, except that the sulfur-based active material is used, and a lithium ion secondary battery can be produced in the same manner as in the production of a general lithium ion secondary battery, except that the electrode for a lithium ion secondary battery is used. The lithium ion secondary battery produced in this manner has a large charge / discharge capacity and excellent cycle characteristics.
[0094] 1. When using sulfur-based active material as the positive electrode active material The lithium ion secondary battery of the present invention can be produced in accordance with a conventional method by using a positive electrode containing the above-mentioned sulfur-based active material (positive electrode active material), a negative electrode, an electrolyte, and, if desired, other members such as a separator.
[0095] (positive electrode) The positive electrode for lithium ion secondary batteries can be prepared in the same manner as the positive electrode for general lithium ion secondary batteries, except that the above-mentioned sulfur-based active material is used as the positive electrode active material. For example, the positive electrode can be prepared by mixing a particulate sulfur-based active material with a conductive assistant, a binder, and a solvent to prepare a paste-like positive electrode material, applying the positive electrode material to a current collector, and then drying the same. In addition, as another method, the positive electrode can also be prepared by kneading the sulfur-based active material with a conductive assistant, a binder, and a small amount of solvent using a mortar or the like, forming it into a film, and then pressing it onto a current collector using a press or the like.
[0096] [Conductive additive] Examples of the conductive assistant include vapor grown carbon fiber (VGCF), carbon powder, carbon black (CB), acetylene black (AB), ketjen black (KB), graphite, or fine powder of a metal such as aluminum or titanium that is stable at a positive electrode potential. These conductive assistants can be used alone or in combination.
[0097] [Binder] Examples of binders include polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyimide (PI), polyamide-imide (PAI), carboxymethyl cellulose (CMC), polyvinyl chloride (PVC), acrylic resin, methacrylic resin (PMA), polyacrylonitrile (PAN), modified polyphenylene oxide (PPO), polyethylene oxide (PEO), polyethylene (PE), polypropylene (PP), etc. These binders can be used alone or in combination of two or more.
[0098] [solvent] Examples of the solvent include N-methyl-2-pyrrolidone, N,N-dimethylformaldehyde, alcohol, hexane, water, etc. These solvents can be used alone or in combination of two or more.
[0099] [Amount] The amounts of the materials constituting the positive electrode are not particularly limited, but for example, it is preferable to mix 2 parts by mass or more and 100 parts by mass or less of a conductive assistant, 2 parts by mass or more and 50 parts by mass or less of a binder, and an appropriate amount of a solvent with respect to 100 parts by mass of a sulfur-based active material.
[0100] [Current collector] As the current collector, one generally used for the positive electrode of a lithium ion secondary battery may be used. For example, the current collector may be made of aluminum foil, aluminum mesh, punched aluminum sheet, aluminum expand sheet, stainless steel foil, stainless steel mesh, punched stainless steel sheet, stainless steel expand sheet, foamed nickel, nickel nonwoven fabric, copper foil, copper mesh, punched copper sheet, copper expand sheet, titanium foil, titanium mesh, carbon nonwoven fabric, carbon woven fabric, etc. Among these, a current collector made of carbon nonwoven fabric or carbon woven fabric made of carbon with a high degree of graphitization does not contain hydrogen and has low reactivity with sulfur, so it is suitable as a current collector when the sulfur-based active material of the present invention is used as a positive electrode active material. As a raw material for carbon fiber with a high degree of graphitization, various pitches (i.e., by-products of petroleum, coal, coal tar, etc.) and polyacrylonitrile fiber (PAN) that are materials for carbon fiber can be used. In addition to using one type of current collector, two or more types may be used in combination.
[0101] (Negative electrode) As the negative electrode material, known metallic lithium, carbon-based materials such as graphite, silicon-based materials such as silicon thin film, and alloy-based materials such as copper-tin and cobalt-tin can be used. When a material that does not contain lithium, for example, a carbon-based material, silicon-based material, alloy-based material, etc., among the above-mentioned negative electrode materials, is used as the negative electrode material, it is advantageous in that a short circuit between the positive and negative electrodes due to the generation of dendrites is unlikely to occur. However, when these lithium-free negative electrode materials are used in combination with the positive electrode of the present invention, neither the positive electrode nor the negative electrode contains lithium. For this reason, a lithium pre-doping process is required in which lithium is inserted in advance into either or both of the negative electrode and the positive electrode. The pre-doping method of lithium may be according to a known method. For example, when doping lithium into the negative electrode, a method of inserting lithium by an electrolytic doping method in which a half cell is assembled using metallic lithium as the counter electrode and lithium is electrochemically doped, or a method of inserting lithium by a pasting pre-doping method in which a metallic lithium foil is pasted on the electrode and then left in an electrolyte solution to dope the lithium by utilizing the diffusion of lithium into the electrode, can be mentioned. In addition, the above-mentioned electrolytic doping method can be used when pre-doping the positive electrode with lithium. As the negative electrode material that does not contain lithium, silicon-based materials, which are high-capacity negative electrode materials, are particularly preferred, and among them, thin-film silicon, which has a thin electrode thickness and is advantageous in terms of capacity per volume, is more preferred.
[0102] (electrolyte) The electrolyte used in the lithium ion secondary battery may be an organic solvent in which an electrolyte alkali metal salt is dissolved. As the organic solvent, it is preferable to use at least one selected from non-aqueous solvents such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl ether, γ-butyrolactone, and acetonitrile. As the electrolyte, LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiI, LiClO4, etc. may be used. The concentration of the electrolyte may be about 0.5 mol / L or more and 1.7 mol / L or less. The electrolyte is not limited to a liquid state. For example, when the lithium ion secondary battery is a lithium polymer secondary battery, the electrolyte is in a solid state (for example, a polymer gel state).
[0103] (Separator) The lithium ion secondary battery may include a separator and other components in addition to the above-mentioned negative electrode, positive electrode, and electrolyte. The separator is interposed between the positive electrode and the negative electrode, and allows the movement of ions between the positive electrode and the negative electrode, and prevents internal short-circuiting between the positive electrode and the negative electrode. If the lithium ion secondary battery is a sealed type, the separator is also required to have a function of retaining the electrolyte. As the separator, it is preferable to use a thin, microporous or nonwoven membrane made of polyethylene, polypropylene, polyacrylonitrile, aramid, polyimide, cellulose, glass, or the like.
[0104] (shape) The shape of the lithium ion secondary battery is not particularly limited, and it can be in various shapes such as a cylindrical type, a laminated type, a coin type, a button type, and the like.
[0105] 2. When sulfur-based active material is used as the negative electrode active material The lithium ion secondary battery of the present invention can be produced in accordance with a conventional method by using a negative electrode containing the above-mentioned sulfur-based active material (negative electrode active material), a positive electrode, an electrolyte, and, if desired, other members such as a separator.
[0106] (Negative electrode) The negative electrode for lithium ion secondary batteries can be prepared in the same manner as the negative electrode for general lithium ion secondary batteries, except that the sulfur-based active material is used as the negative electrode active material. For example, the negative electrode can be prepared by mixing a particulate sulfur-based active material with a conductive assistant, a binder, and a solvent to prepare a paste-like negative electrode material, applying the negative electrode material to a current collector, and then drying the paste. In addition, as another method, the negative electrode can also be prepared by kneading the sulfur-based active material with a conductive assistant, a binder, and a small amount of solvent using a mortar or the like, forming it into a film, and then pressing it onto a current collector using a press or the like.
[0107] The conductive assistant, binder and solvent can be the same as those used in the above case where the sulfur-based active material is used as the positive electrode active material, and the current collector can also be the same as those used in the above case where the sulfur-based active material is used as the positive electrode active material.
[0108] (positive electrode) The positive electrode material is not particularly limited as long as it is, for example, a transition metal oxide or solid solution oxide containing lithium, or a substance capable of electrochemically absorbing and releasing lithium ions. Examples of the transition metal oxide containing lithium include Li·Co-based composite oxides such as LiCoO2, LiNi x Co y Mn z Examples of the solid solution oxide include Li·Ni·Co·Mn-based composite oxides such as LiO2, Li·Ni-based composite oxides such as LiNiO2, and Li·Mn-based composite oxides such as LiMn2O4. a Mn x Co y Ni z O2 (1.150≦a≦1.430, 0.450≦x≦0.600, 0.100≦y≦0.150, 0.200≦z≦0.280), LiMn x Co y Ni z O2 (0.300≦x≦0.850, 0.100≦y≦0.300, 0.100≦z≦0.300), LiMn 1.5 Ni 0.5O4, etc. These compounds may be used alone or in combination of two or more kinds.
[0109] The electrolyte, separator, and shape of the lithium ion secondary battery can be the same as those in the above case where a sulfur-based active material is used as the positive electrode active material. EXAMPLES
[0110] The present invention will be described based on examples, but the present invention is not limited to only the examples.
[0111] The various chemicals used in the Examples and Comparative Examples are listed below. The various chemicals were purified according to conventional methods as necessary.
[0112] <Materials used in the test> Acrylic resin 1: Spherical acrylic resin consisting of a homopolymer of methyl methacrylate (Techpolymer MB-4 manufactured by Sekisui Chemical Co., Ltd., particle size: 4 μm) Iron compound 1 (organic acid salt): Iron(II) oxalate dihydrate (Iron(II) oxalate dihydrate, special grade, manufactured by Kanto Chemical Co., Ltd.) Iron compound 2 (organic acid salt): Iron(II) acetate (Iron(II) acetate manufactured by Kanto Chemical Co., Ltd.) Sulfur: Precipitated sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Organic solvent (WET method): Acetone (Yoneyama Pharmaceutical Co., Ltd., acetone, special grade)
[0113] Production Example 1 (Fine Grinding of Iron Compounds) Before being subjected to the kneading step, the iron compound was ground in advance, as necessary, using a freeze grinder (JFC-2000 manufactured by Japan Analytical Industry Co., Ltd.), a cutter mill (Free Speed Mill FS-20 manufactured by LabNect Co., Ltd.) or a dry jet mill (Nano Jet Mizer NJ-30 manufactured by Aisin Nano Technologies Co., Ltd.) as shown in Table 1 below.
[0114] [Table 1]
[0115] Production Example 2 (Preparation of raw materials by the WET method) According to the formulation in Table 3, an acrylic resin was added to an organic solvent and mixed thoroughly, and then an iron compound was added and mixed to obtain a liquid mixture. Next, the organic solvent was removed from the liquid mixture, and the mixture was pulverized with a cutter mill (LAB MILL manufactured by Osaka Chemical Co., Ltd.) to obtain a dry mixture.
[0116] The thus obtained dry mixture and sulfur were mixed in a blender to obtain a raw material for calcination.
[0117] In Comparative Example 2, the acrylic resin 1 and sulfur, and in Comparative Example 3, the iron compound 1 and sulfur were mixed in a blender to prepare a raw material for firing.
[0118] Example 1 <Production of sulfur-based active materials> (Ingredients for firing) As shown in Table 3, the raw materials prepared by the WET method described above were used as the raw materials for firing.
[0119] (Reaction Apparatus) The raw materials were fired using a reaction apparatus 1 shown in Fig. 1. The reaction apparatus 1 includes a cylindrical reaction vessel 3 made of quartz glass with a bottom, an outer diameter of 60 mm, an inner diameter of 50 mm, and a height of 300 mm, for storing and firing the raw materials 2, a silicone lid 4 for closing the upper opening of the reaction vessel 3, an alumina protective tube 5 ("Alumina SSA-S" manufactured by Nikkato Corporation, outer diameter 4 mm, inner diameter 2 mm, length 250 mm) that penetrates the lid 4, two gas inlet tubes 6 and a gas outlet tube 7 (both manufactured by Nikkato Corporation, "Alumina SSA-S" manufactured by Nikkato Corporation, outer diameter 6 mm, inner diameter 4 mm, length 150 mm), and an electric furnace 8 (crucible furnace, opening width φ80 mm, heating height 100 mm) for heating the reaction vessel 3 from the bottom side.
[0120] The alumina protective tube 5 is formed to a length that extends downward from the lid 4 to the raw material 2 contained at the bottom of the reaction vessel 3, and a thermocouple 9 is inserted inside. The alumina protective tube 5 is used as a protective tube for the thermocouple 9. The tip of the thermocouple 9 is inserted into the raw material 2 while being protected by the closed tip of the alumina protective tube 5, and functions to measure the temperature of the raw material 2. The output of the thermocouple 9 is input to a temperature controller 10 of the electric furnace 8, as shown by the solid arrow in the figure, and the temperature controller 10 functions to control the heating temperature of the electric furnace 8 based on the input from this thermocouple 9.
[0121] The gas inlet pipe 6 and the gas outlet pipe 7 are formed so that their lower ends protrude downward from the lid 4 by 3 mm. Ar (argon) gas is continuously supplied to the gas inlet pipe 6 from a gas supply system (not shown). The gas outlet pipe 7 is connected to a trap tank 12 containing an aqueous sodium hydroxide solution 11. Exhaust air attempting to exit the reaction vessel 3 through the gas outlet pipe 7 passes through the aqueous sodium hydroxide solution 11 in the trap tank 12 before being released to the outside. Therefore, even if the exhaust air contains hydrogen sulfide gas generated by the vulcanization reaction, it is neutralized with the aqueous sodium hydroxide solution and removed from the exhaust air.
[0122] (Firing process) First, with the raw material 2 accommodated at the bottom of the reaction vessel 3, Ar gas was continuously supplied from the gas supply system at a flow rate of 80 mL / min, and 30 minutes after the start of the supply, heating was started in the electric furnace 8. The temperature was increased at a rate of 150°C / h. When the temperature of the raw material reached the firing temperature (400°C) in Table 3, firing was performed for 2 hours while maintaining the firing temperature. Next, the temperature of the reaction product was naturally cooled to 25°C under an Ar gas atmosphere while adjusting the flow rate of Ar gas, and the product was then removed from the reaction vessel 3.
[0123] (Removal of unreacted sulfur) In order to remove the unreacted sulfur (free sulfur) remaining in the product after the firing process, the following process was carried out. That is, the product was crushed in a mortar, and 2 g of the crushed material was placed in a glass tube oven and heated at 250°C for 3 hours while vacuum suction was applied to obtain a sulfur-based active material from which the unreacted sulfur had been removed (or which contained only a trace amount of unreacted sulfur). The heating rate was 10°C / min.
[0124] (Classification process) In order to remove coarse particles from the fired product, the product was classified using a stainless steel sieve with a mesh size of 32 μm to obtain a sulfur-based active material.
[0125] <Production of lithium-ion secondary battery> A lithium ion secondary battery was fabricated as follows.
[0126] (positive electrode) The sulfur-based active material obtained above was used as the active material, acetylene black as the conductive assistant, and acrylic resin as the binder. These were weighed so that the ratio of active material:conductive assistant:binder was 90:5:5 (mass%), placed in a container, and stirred and mixed using a centrifugal mixer (ARE-250 made by Thinky Corporation) using milliQ water as a dispersant to prepare a uniform slurry. The prepared slurry was applied to an aluminum foil of 20 μm using an applicator with a slit width of 60 μm, and the electrode compressed using a roll press was heated in a dryer at 120 ° C for 3 hours, dried, and punched out to φ11 to obtain an electrode (positive electrode). The mass of the electrode was then measured, and the amount of active material in the electrode was calculated from the above ratio.
[0127] (Negative electrode) As the negative electrode, a metallic lithium foil (disk-shaped with a diameter of 14 mm and a thickness of 500 μm, manufactured by Honjo Metals Co., Ltd.) was used.
[0128] (electrolyte) The electrolyte used was a non-aqueous electrolyte in which LiPF6 was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate. The ethylene carbonate and diethyl carbonate were mixed in a volume ratio of 1:1. The concentration of LiPF6 in the electrolyte was 1.0 mol / L.
[0129] (Lithium-ion secondary battery) A coin battery was produced using the above positive and negative electrodes. In detail, in a dry room, a separator (Celgard2400 manufactured by Celgard, a polypropylene microporous membrane having a thickness of 25 μm) and a glass nonwoven fabric filter (440 μm thick, GA100 manufactured by ADVANTEC) were sandwiched between the positive and negative electrodes to produce an electrode body battery. This electrode body battery was housed in a battery case (a member for CR2032 type coin batteries, manufactured by Hosen Co., Ltd.) made of a stainless steel container. The above electrolyte was injected into the battery case. The battery case was sealed with a crimping machine to obtain the lithium ion secondary battery of Example 1.
[0130] Examples 2 to 5 and Comparative Examples 1 to 4 Except for making appropriate changes according to Table 3, the same treatment as in Example 1 was carried out to prepare the respective raw materials, sulfur-based active materials, and lithium-ion secondary batteries.
[0131] <Measurement of discharge capacity and capacity retention rate> The coin-type lithium-ion secondary batteries produced in each Example and Comparative Example were charged and discharged at a current value equivalent to 50 mA for the first to ninth times per 1 g of positive electrode active material, and at a current value equivalent to 100 mA for the tenth to thirtieth times, under the condition of a test temperature of 30° C. The discharge end voltage was 1.0 V, and the charge end voltage was 3.0 V. The charge and discharge were repeated, and the battery discharge capacity (mAh) was observed for the 10th and 30th times.
[0132] The second discharge capacity (mAh / g) was taken as the initial capacity. The larger the initial capacity, the greater the charge / discharge capacity of the lithium-ion secondary battery, and the more favorable it is. 10 (mAh / g) and 30th discharge capacity DC 30From (mAh / g), the following formula (a): Capacity maintenance rate (%)=(DC 30 / DC 10 )×100 (a) As explained above, the higher the capacity retention rate, the better the cycle characteristics of the lithium-ion secondary battery.
[0133] <Elemental analysis> The sulfur-based active materials produced in the examples and comparative examples were subjected to elemental analysis.
[0134] The mass ratio (%) of carbon, hydrogen, sulfur, and nitrogen in the total amount of the sulfur-based active material was calculated from the mass measured using a fully automatic elemental analyzer vario MICRO cube manufactured by Elementar. The results are shown in Table 3.
[0135] <True density> The sulfur-based active materials produced in the examples and comparative examples were subjected to thermogravimetry, and the true density (g / cm 3 ) was calculated.
[0136] The apparatus used for the thermogravimetric measurement was a TGA Q500 manufactured by TA Instruments. The measurement conditions were heating to 750°C in an Ar atmosphere, and then introducing air to completely decompose the measurement sample. The ash ratio (wt%) was then calculated from the measured weight loss rate (wt%). The weight loss rate of Comparative Example 2 shows that the acrylic resin sulfide is completely decomposed, and the weight loss rate of Comparative Example 3 shows that iron disulfide (FeS2) is reduced by 36% by weight. The true density of the acrylic resin sulfide of Comparative Example 2 was 1.8 g / cm 3 (actual measured value). On the other hand, the true density of the iron disulfide of Comparative Example 3 was 5.0 g / cm 3 (Literature value) was used. The true density of the sulfur-based active material was calculated from the obtained value using the following formula. True density of sulfur-based active material (g / cm 3)=(A+B) / (A / 1.8+B / 5.0) A: Weight ratio of acrylic resin sulfide (% by weight) B: Weight ratio of iron disulfide (% by weight)
[0137] The results are shown in Table 2 below.
[0138] [Table 2]
[0139] <Median diameter> The volume-based cumulative 50% diameter (median diameter D50) was measured using a laser diffraction / scattering particle size distribution analyzer (Anton Paar, particle size distribution analyzer PSA1090L) with water as the dispersion medium.
[0140] [Table 3]
[0141] <Embodiment> The following are preferred embodiments.
[0142] [1] (1) A process for obtaining a raw material by mixing an acrylic resin, sulfur, and an iron compound containing a divalent or trivalent iron ion; and (2) A step of calcining the raw material A method for producing a sulfur-based active material comprising: a production method in which the median diameter of the iron compound is 12.00 μm or less, preferably 10.00 μm or less, more preferably 8.00 μm or less, even more preferably 6.00 μm or less, even more preferably 5.00 μm or less, even more preferably 4.50 μm or less, even more preferably 4.30 μm or less, even more preferably 4.29 μm or less, even more preferably 4.00 μm or less, even more preferably 3.00 μm or less; [2] The method for producing a sulfur-based active material according to the above [1], wherein the content of the iron compound containing the divalent or trivalent iron ion in the raw material is 50 parts by mass or more and 300 parts by mass or less, preferably more than 60 parts by mass and less than 250 parts by mass, more preferably more than 70 parts by mass and less than 200 parts by mass, even more preferably more than 75 parts by mass and less than 150 parts by mass, and even more preferably more than 75 parts by mass and less than 100 parts by mass, relative to 100 parts by mass of the acrylic resin. [3] The step (1), (1-a-1) a step of adding the acrylic resin and the iron compound containing divalent or trivalent iron ions to an organic solvent and mixing them to obtain a liquid mixture; (1-a-2) removing the organic solvent from the liquid mixture to obtain a dry mixture; and (1-a-3) mixing the dry mixture with sulfur The method for producing a sulfur-based active material according to the above [1] or [2], [4] The step (1), (1-b) a step of mixing the acrylic resin, the sulfur, and the iron compound containing divalent or trivalent iron ions, all in a powder state. The method for producing a sulfur-based active material according to the above [1] or [2], [5] The method for producing a sulfur-based active material according to any one of the above [1] to [4], wherein the temperature of the calcination in the step (2) is more than 250° C. and less than 550° C., preferably more than 300° C. and less than 500° C., more preferably more than 350° C. and less than 450° C., and further preferably more than 380° C. and less than 450° C.; [6] The method for producing a sulfur-based active material according to any one of the above [1] to [5], wherein the firing temperature in the step (2) is higher than a temperature at which the iron compound containing divalent or trivalent iron ions is thermally decomposed. [7] The method for producing a sulfur-based active material according to any one of the above [1] to [6], wherein the content of the sulfur in the raw material is more than 50 parts by mass and less than 1000 parts by mass, preferably more than 100 parts by mass and less than 900 parts by mass, more preferably more than 300 parts by mass and less than 800 parts by mass, further preferably more than 400 parts by mass and less than 700 parts by mass, and further preferably more than 500 parts by mass and less than 700 parts by mass, relative to 100 parts by mass of the acrylic resin. [8] The method for producing a sulfur-based active material according to any one of the above [1] to [7], wherein the acrylic resin is at least one polymer selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one polymer selected from the group consisting of polymers of at least one compound selected from the group consisting of acrylate compounds represented by the following formula (1) and at least one compound selected from the group consisting of diacrylate compounds represented by the following formula (2), CH2=C(R 11 )COOR 12 (1) (where R 11 is a hydrogen atom or a methyl group, and R 12 is an alkyl group. CH2=C(R 21 )COO-Y-OCO(R 22 )C=CH2(2) (where R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms. [9]R 12is an alkyl group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, preferably 2 or 3 carbon atoms, in which the hydrocarbylene group has 1 to 4 substituents, preferably 1 or 2, the alkyl group as the substituent has 1 to 4 carbon atoms, preferably 1, and the carbon skeleton constituting the hydrocarbylene group has 1 to 2 ether bonds.
[10] After producing a sulfur-based active material by the method for producing a sulfur-based active material according to any one of [1] to [9] above, (3) A step of preparing an electrode using the sulfur-based active material by a conventional method. A method for producing an electrode, comprising:
[11] After producing an electrode by the method for producing an electrode according to the above
[10] , (4) A step of producing a lithium ion secondary battery using the electrode by a conventional method. A method for producing a lithium ion secondary battery,
[12] A sulfur-based active material comprising at least carbon, sulfur, and iron as constituent elements, the sulfur-based active material being obtained by firing a raw material comprising an acrylic resin, sulfur, and an iron compound comprising divalent or trivalent iron ions, wherein the median diameter of the iron compound is 12.00 μm or less, preferably 10.00 μm or less, more preferably 8.00 μm or less, even more preferably 6.00 μm or less, even more preferably 5.00 μm or less, even more preferably 4.50 μm or less, even more preferably 4.30 μm or less, even more preferably 4.29 μm or less, even more preferably 4.00 μm or less, even more preferably 3.00 μm or less; Contains iron disulfide, The content of sulfur as a constituent element is 40.0 mass% or more, preferably 45.0 mass% or more, more preferably 50.0 mass% or more, and even more preferably 55.0 mass% or more. sulfur-based active material,
[13] The sulfur-based active material according to
[12] above, in which the half-width of the peak showing the maximum diffraction intensity within the range of 2θ=33.04° (±1.0°) is 0.20° or more in an X-ray diffraction measurement using CuKα radiation;
[14] True density is 2.4g / cm 3 Super 3.6g / cm 3 Less than 2.5 g / cm 3 Super 3.5g / cm 3 less than 2.6 g / cm 3 More than 3.2g / cm 3 less than 2.6 g / cm 3 Super 3.2g / cm 3 less than 2.6 g / cm 3 Super 3.1g / cm 3 The sulfur-based active material according to the above
[12] or
[13] ,
[15] The sulfur-based active material according to any one of the above
[12] to
[14] , wherein the carbon content is more than 5.0% by mass and less than 30.0% by mass, preferably more than 6.0% by mass and less than 29.0% by mass, more preferably more than 7.0% by mass and less than 25.0% by mass, even more preferably more than 8.0% by mass and less than 25.0% by mass, and even more preferably more than 8.5% by mass and less than 25.0% by mass.
[16] The sulfur-based active material according to any one of
[12] to
[15] above, which has peaks at 2θ=25.5° (±1.0°), 28.51° (±1.0°), 33.04° (±1.0°), 37.07° (±1.0°), 40.76° (±1.0°), 47.42° (±1.0°), and 56.27° (±1.0°) in an X-ray diffraction measurement using CuKα radiation;
[17] The sulfur-based active material according to any one of the above
[12] to
[16] , wherein the acrylic resin is at least one polymer selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one polymer selected from the group consisting of polymers of at least one compound selected from the group consisting of acrylate compounds represented by the following formula (1) and at least one compound selected from the group consisting of diacrylate compounds represented by the following formula (2): CH2=C(R 11 )COOR 12 (1) (where R 11 is a hydrogen atom or a methyl group, and R 12 is an alkyl group. CH2=C(R 21 )COO-Y-OCO(R 22 )C=CH2(2) (where R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms.
[18] R 12 is an alkyl group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, and Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, preferably 2 or 3 carbon atoms, in which the hydrocarbylene group has 1 to 4 substituents, preferably 1 or 2, the alkyl group as the substituent has 1 to 4 carbon atoms, preferably 1, and the carbon skeleton constituting the hydrocarbylene group has 1 to 2 ether bonds.
[19] The sulfur-based active material according to any one of the above
[12] to
[18] , having a median diameter of 1 μm or more and 40 μm or less, preferably more than 2 μm and less than 30 μm, more preferably more than 3 μm and less than 20 μm, even more preferably more than 4 μm and less than 15 μm, and even more preferably more than 4 μm and less than 10 μm.
[20] The content of the iron compound containing the divalent or trivalent iron ion and the content of the sulfur in the raw material are, relative to 100 parts by mass of the acrylic resin, 50 parts by mass or more and 300 parts by mass or less, preferably more than 60 parts by mass but less than 250 parts by mass, more preferably more than 70 parts by mass but less than 200 parts by mass, even more preferably more than 75 parts by mass but less than 150 parts by mass, even more preferably more than 75 parts by mass but less than 100 parts by mass, and more than 50 parts by mass but less than 1,000 parts by mass, preferably more than 100 parts by mass but less than 900 parts by mass, more preferably more than 300 parts by mass but less than 800 parts by mass, even more preferably more than 400 parts by mass but less than 700 parts by mass, and even more preferably more than 500 parts by mass but less than 700 parts by mass. The sulfur-based active material according to any one of
[12] to
[19] above. [Explanation of symbols]
[0143] 1. Reactor 2 Raw materials 3 Reaction vessel 4 Silicone lid 5 Alumina protection tube 6 Gas inlet pipe 7 Gas exhaust pipe 8. Electric Furnace 9 Thermocouples 10 Temperature Controller 11 Sodium hydroxide solution 12 Trap tank
Claims
1. (1) A step of mixing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions to obtain a raw material; and (2) A step of calcining the raw material A method for producing a sulfur-based active material comprising: The manufacturing method, wherein the median diameter of the iron compound is 12.00 μm or less.
2. The method for producing a sulfur-based active material according to claim 1, wherein the content of the iron compound containing the divalent or trivalent iron ion in the raw material is 50 parts by mass or more and 300 parts by mass or less with respect to 100 parts by mass of the acrylic resin.
3. The step (1), (1-a-1) a step of introducing the acrylic resin and the iron compound containing divalent or trivalent iron ions into an organic solvent and mixing them to obtain a liquid mixture; (1-a-2) removing the organic solvent from the liquid mixture to obtain a dry mixture; and (1-a-3) A step of mixing the dry mixture with sulfur The method for producing a sulfur-based active material according to claim 1 or 2, comprising:
4. The step (1), (1-b) A step of mixing the acrylic resin, the sulfur, and the iron compound containing divalent or trivalent iron ions, all in a powder state. The method for producing a sulfur-based active material according to claim 1 or 2, comprising:
5. The method for producing a sulfur-based active material according to claim 1 or 2, wherein the firing temperature in the step (2) is higher than 250°C and lower than 550°C.
6. The method for producing a sulfur-based active material according to claim 1 or 2, wherein the firing temperature in the step (2) is higher than a temperature at which the iron compound containing the divalent or trivalent iron ion is thermally decomposed.
7. The method for producing a sulfur-based active material according to claim 1 or 2, wherein the content of the sulfur in the raw material is more than 50 parts by mass and less than 1000 parts by mass with respect to 100 parts by mass of the acrylic resin.
8. The acrylic resin is a polymer obtained by polymerizing at least one selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one selected from the group consisting of acrylate compounds represented by the following formula (1) and at least one selected from the group consisting of diacrylate compounds represented by the following formula (2). The method for producing a sulfur-based active material according to claim 1 or 2. CH 2 =C(R 11 )COOR 12 (1) (Here, R 11 is a hydrogen atom or a methyl group, R 12 is an alkyl group.) CH 2 =C(R 21 )COO-Y-OCO(R 22 )C=CH 2 (2) (Here, R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms.
9. R 12 is an alkyl group having 1 to 6 carbon atoms, Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, the hydrocarbylene group has 1 to 4 substituents, the alkyl group as the substituent has 1 to 4 carbon atoms, and the carbon skeleton constituting the hydrocarbylene group has 1 to 2 ether bonds. The method for producing a sulfur-based active material according to claim 8.
10. After producing a sulfur-based active material by the method for producing a sulfur-based active material according to claim 1 or 2, (3) A step of preparing an electrode using the sulfur-based active material by a conventional method. A method for producing an electrode comprising the steps of:
11. After the electrode is produced by the method for producing an electrode according to claim 10, (4) A step of producing a lithium ion secondary battery using the electrode by a conventional method. The method for producing a lithium ion secondary battery comprises the steps of:
12. A sulfur-based active material containing at least carbon, sulfur, and iron as constituent elements, the sulfur-based active material being obtained by firing a raw material containing an acrylic resin, sulfur, and an iron compound containing divalent or trivalent iron ions, the iron compound having a median diameter of 12.00 μm or less, Contains iron disulfide, The content of sulfur as a constituent element is 40.0 mass% or more. Sulfur-based active material.
13. The sulfur-based active material according to claim 12, wherein the half-width of a peak showing a maximum diffraction intensity within a range of 2θ = 33.04 ° (± 1.0 °) is 0.20 ° or more in an X-ray diffraction measurement using CuKα rays.
14. True density is 2.4 g / cm 3 Super 3.6g / cm 3 The sulfur-based active material according to claim 12 or 13, wherein the sulfur-based active material has a molecular weight of less than 10000.
15. The sulfur-based active material according to claim 12 or 13, wherein the carbon content is more than 5.0% by mass and less than 30.0% by mass.
16. In an X-ray diffraction measurement using CuKα radiation, the sulfur-based active material according to claim 12 or 13 has peaks at 2θ = 25.5 ° (± 1.0 °), 28.51 ° (± 1.0 °), 33.04 ° (± 1.0 °), 37.07 ° (± 1.0 °), 40.76 ° (± 1.0 °), 47.42 ° (± 1.0 °), and 56.27 ° (± 1.0 °).
17. The acrylic resin is a polymer obtained by polymerizing at least one selected from the group consisting of acrylate compounds represented by the following formula (1), or at least one selected from the group consisting of acrylate compounds represented by the following formula (1) and at least one selected from the group consisting of diacrylate compounds represented by the following formula (2). The sulfur-based active material according to claim 12 or 13. CH 2 =C(R 11 )COOR 12 (1) (Here, R 11 is a hydrogen atom or a methyl group, R 12 is an alkyl group.) CH 2 =C(R 21 )COO-Y-OCO(R 22 )C=CH 2 (2) (Here, R 21 and R 22 are the same or different and each is a hydrogen atom or a methyl group, and Y is a linear hydrocarbylene group, which may have at least one substituent selected from the group consisting of a hydroxyl group and an alkyl group, and the carbon skeleton constituting the hydrocarbylene group may have an ether bond via an oxygen atom. However, when there are two or more ether bonds, there are always two or more carbon atoms between adjacent oxygen atoms.
18. R 12 is an alkyl group having 1 to 6 carbon atoms, Y is a linear hydrocarbylene group having 2 to 6 carbon atoms, the hydrocarbylene group has a number of substituents of 1 to 4, the alkyl group as the substituent has a carbon number of 1 to 4, and the carbon skeleton constituting the hydrocarbylene group has a number of ether bonds of 1 to 2. The sulfur-based active material according to claim 17.
19. The sulfur-based active material according to claim 12 or 13, having a median diameter of 1 μm or more and 40 μm or less.
20. The content of the iron compound containing the divalent or trivalent iron ion and the content of the sulfur in the raw material are 50 parts by mass or more and 300 parts by mass or less and more than 50 parts by mass or less than 1000 parts by mass, respectively, relative to 100 parts by mass of the acrylic resin. The sulfur-based active material according to claim 12 or 13.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery and manufacturing method thereof
JP2012248549A
Method for manufacturing positive electrode for nonaqueous electrolyte secondary battery, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2013054957A
Sulfur-based active material
JP2020167144A
Composite sulfide electrode and manufacturing method
JP2022517877A
Positive electrode for lithium ion secondary batteries, lithium ion secondary battery, method of producing a positive electrode for lithium ion secondary batteries, and vehicle
WO2012098614A1